1999
DOI: 10.1016/s0370-2693(99)00450-5
|View full text |Cite
|
Sign up to set email alerts
|

Central production of mesons: Exotic states versus Pomeron structure

Abstract: We demonstrate that the azimuthal dependence of central meson production in hadronic collisions, when suitably binned, provides unambiguous tests of whether the Pomeron couples like a conserved vector-current to protons. We discuss the possibility of discriminating between qq and glueball production in such processes. Our predictions apply also to meson production in tagged two-photon events at electron-positron colliders and to vector-meson production in ep collisions at HERA.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
3
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 10 publications
(17 reference statements)
2
38
3
1
Order By: Relevance
“…The dk T (or ) dependence of central production has been studied intensively in nearly all WA102 publications; its implications are discussed in a series of papers by Close and collaborators [739,[742][743][744][745][746][747]. The study revealed two surprises.…”
Section: Central Productionmentioning
confidence: 99%
“…The dk T (or ) dependence of central production has been studied intensively in nearly all WA102 publications; its implications are discussed in a series of papers by Close and collaborators [739,[742][743][744][745][746][747]. The study revealed two surprises.…”
Section: Central Productionmentioning
confidence: 99%
“…Helicity 2 is suppressed by Bose symmetry 60 and has been found to be negligible experimentally 68 . The structure of the cross section is then predicted to be dominantly in helicity-one.…”
Section: When This Quantity (Dpmentioning
confidence: 98%
“…The calculations have been described in [8,9] and the resulting behaviour of the cross section may be summarised as follows:…”
Section: ++mentioning
confidence: 99%